Ultra Wideband (UWB) Multiple Input and Multiple Output (MIMO) Antenna Design : A Review - Firdaus Firdaus; Rahmadi Kurnia; Ikhwana Elfitri (Andalas Journal of Electrical and Electronic Engineering Technology, 2023)
Since the Federal Communication Commission (FCC) issued a license for the 3.1 – 10.6 GHz frequency spectrum for unlicensed radio applications, many papers have been published regarding ultrawideband (UWB) antenna design. The issue of UWB antenna design is determining how to create an antenna with a wide bandwidth, capable of rejecting communication systems that coexist with UWB bands, and capable of designing UWB antennas for multiple input multiple output (MIMO) communication system applications. This study examines the design of UWB antennas with monopole and slot types based on evaluations published over the last two decades. The discussion began with UWB and MIMO systems and then moved on to the configuration of monopole and slot UWB antennas. UWB antenna layout with notched bands and the several types of notched bands available. Finally, two port and quad-port MIMO antenna configuration is examined. To further understand UWB antenna design, numerous UWB antenna configurations are simulated. The outcomes of this review can be utilized as preliminary reading material for researchers looking into UWB antennas.